VISUALISASI RAGAM KARAKTER IKONIK KARYA PATUNG I WAYAN MAWAN DI DESA BURUAN KECAMATAN BLAHBATUH KABUPATEN GIANYAR - I Gede Pasek; I Nyoman Sila; I Wayan Sudiarta (Jurnal Pendidikan Seni Rupa Undiksha, 2021)
The research aims to discuss (1) a story theme that is visualized on the works of statue I Wayan Mawan, (2) the typical iconography that I Wayan Mawan visualize on his sculptures to make it easier to identify the narratives each on creates, (3) the processing and regulating of typical iconography of each narrative on the sculpture by I Wayan Mawan. The research subject is I Wayan Mawan was a sculptor born in  Buruan Village, Blahbatuh, Gianyar City. In the study using qualitative descriptive research. The research employs three methods of data collection such as observation, interview, and documentation. The result in research was (1) The themes visualized in I Wayan Mawan's sculptures are the Mahabharata and Ramayana epics, the study of iconography of I Wayan Mawan's sculptures identifies elements of the visual aspects of I Wayan Mawan's works,(2) Typical iconography visualized by I Wayan Mawan Wayan Mawan in his sculptures to make it easier to identify the narrative contained are the visual aspects that raise the epics of Mahabharata and Ramayana in each of his statues, (3) Processing and arrangement of iconography in each of his statues using decorative techniques and following the shape of the wood when creating characters of each statue.